Metal Complexes of 4, 4′-Bipyridine: Characterization, Electrochemical Performance and Application in High Sensitivity Detection of H2O2. Issue 9 (1st January 2016) - Dong, Sheying; Peng, Lei; Suo, Gaochao; Wei, Wenbo; Huang, Tinglin
Abstract : Three metal complexes composed of divalent transition metals such as Cu(II), Ni(II) and Co(II) metal ions from their corresponding aqueous salt and 4, 4 ′ -Bipyridine (BPy) were prepared by hydrothermal reaction in a Teflon-lined autoclave, and were also characterized by Fourier transform infrared spectra (FT-IR), UV-vis spectra and scanning electron microscopy (SEM). Furthermore, they were effectively used to prepare modified carbon paste electrodes (M-BPy/CPE) to investigate electrochemical performances of these complexes by electrochemical impedance spectroscopy (EIS) and Cyclic voltammograms (CVs). It was found that hydrogen peroxide (H2 O2 ) could inhibit the electron transfer of M-BPy complexes on the electrode surface due to the generation of M-BPy complexs N-oxide. Based on these results, no need for enzyme immobilization, Cu-BPy/CPE was used to construct electrochemical sensor platform for direct detection of H2 O2 . A good linear relationship between peak current inhibition rate and concentration logarithm of H2 O2 was obtained on Cu-BPy/CPE in the range of 2.0 × 10 −9 –2.0 × 10 −3 M with the limit of quantification (LOQ) of 2.3 × 10 −9 M (S/N = 10) and the limit of detection (LOD) of 7.0 × 10 −10 M (S/N = 3). Furthermore, the developed sensor was successfully applied in the determination of H2 O2 in human serum samples with the recoveries from 93.6% ∼ 99.3%.